1993
DOI: 10.1002/fld.1650161002
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of vortex shedding past triangular cylinders at high Reynolds number using a k‐ε turbulence model

Abstract: SUMMARYCalculations of unsteady turbulent flow around and behind triangular-shaped flameholders using a finite volume code with a k--E model of turbulence are presented.The flow behind the flameholders is found to be unsteady (a von Kirman vortex street appears) with a well defined Strouhal frequency (predicted Sr =0.27 compared with an experimental value of 0.25). The predicted profiles of velocity and fluctuating kinetic energy agree well with experiments. The periodic motions in the vortex street are shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(27 citation statements)
references
References 7 publications
0
27
0
Order By: Relevance
“…In contrast to the research related to the flow past circular and rectangular section cylinders, there are limited studies that focus on a triangular cylinder immersed in a uniform flow because the triangular prism is seldom used in building structures. Several researchers have emphasized the influence of the wind direction and the cross-sectional shape on the flow past a triangular cylinder [23][24][25][26]. They demonstrated that the fluctuating cross-flow forces connected with the vortex shedding vary significantly with the incident flow orientation and the aspect ratio.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the research related to the flow past circular and rectangular section cylinders, there are limited studies that focus on a triangular cylinder immersed in a uniform flow because the triangular prism is seldom used in building structures. Several researchers have emphasized the influence of the wind direction and the cross-sectional shape on the flow past a triangular cylinder [23][24][25][26]. They demonstrated that the fluctuating cross-flow forces connected with the vortex shedding vary significantly with the incident flow orientation and the aspect ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Bao et al (2010) considered flow over an equilateral triangular cylinder with different incidence angles at low Reynolds number range. Johansson et al (2010) studied the vortex shedding past triangular cylinders using a k-ε model of turbulence. Wei et al (2016) developed an hybrid RANS/LES model to simulate the complex turbulent flow around a triangular cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…This challenge comes from the fact that the separation is induced by the shock wave and not the geometry. Although URANS is shown to be pretty successful in predicting shedding from bluff bodies, 6 it becomes less reliable in problems where separation is caused otherwise. Flow oscillation over the circular arc airfoil is solved before using very primitive turbulence models like Baldwin-Lomax in two dimensions 5 but to the knowledge of the authors, it has never been solved by more advanced turbulence models such as SA or SST turbulence models as well as more complex models like DES.…”
Section: Introductionmentioning
confidence: 99%